Bilingual Module Innovation with Saintific-Based Regulated Learning Self Strategy - Erie Agusta; Nita Nuraini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
This study aimed to (1) find out the feasibility of the SRLBS bilingual module, and (2) find out the difference between the final results of the bilingual SRLBS module learning with conventional learning. The research method consists of (1) research and information collection; (2) planning; (3) develop preliminary form of product; (4) preliminary field testing; (5) main product revision; (6) main field testing; (7) operational product revision; (8) operational field testing; (9) final product revision; and (10) dissemination and implementation. This study used data analysis techniques Djemari Mardapi for feasibility of product and t-test for the determination of the hypothesis (paired sample t-test & paired sample correlation). The results obtained in the form of (1) bilingual SRLBS module products have been categorized as feasible according to expert judgment, and (2) the module (SRLBS) has the potential to impact students in the form of improved metacognitive abilities, cognitive abilities, and foreign languages.